A Computational Investigation of OME‐synthesis through Homogeneous Acid Catalysis. Issue 7 (5th March 2019) - Goncalves, Tiago J.; Plessow, Philipp N.; Studt, Felix
Abstract: The reaction mechanism of the synthesis of OMEs with homogeneous Brønsted acid catalysts from dimethoxy methane and trioxane is studied using MP2, density functional theory and implicit solvation models. Additionally, formaldehyde is considered as a reactant and we find its activation barriers for OME‐formation to be comparable with those for trioxane (around 80 kJ/mol). If trioxane is used as a reactant at room temperature, we find that its direct incorporation is more favorable than its decomposition to formaldehyde followed by stepwise reaction of formaldehyde. This is due to the higher stability of trioxane at room temperature. Abstract : Computational Investigation : The reaction mechanism of the synthesis of OMEs with homogeneous Brønsted acid catalysts from dimethoxy methane and trioxane is studied using MP2, density functional theory and implicit solvation models.